Magnetism, optical, and thermoelectric response of CdFe2O4 by using DFT scheme. (March 2018) - Mahmood, Q; Yaseen, M; C Bhamu, K; Mahmood, Asif; Javed, Y; M Ramay, Shahid
Abstract: Comparative analysis of electronic, magnetic, optical, and thermoelectric properties of CdFe2 O4, calculated by employing PBEsol + mBJ has been done. The PBEsol reveals metallic nature, while TB-mBJ illustrates ferromagnetic semiconducting behavior. The reasons behind the origin of ferromagnetism are explored by observing the exchange, crystal field, and John–Teller energies. The optical nature is investigated by analyzing dielectric constants, refraction, absorption coefficient, reflectivity, and optical conductivity. Finally, thermoelectric properties are elaborated by describing the electrical and thermal conductivities, Seebeck coefficient, and power factor. The strong absorption for the visible energy and high power factor suggest CdFe2 O4 as the potential candidate for renewable energy applications.